Sosialisasi dan Edukasi Alur pelayanan Pasien Rawat Jalan di RSIA Sitti Khadijah 1 Muhammadiyah Cabang Makassar - Windarti, Sriyani; Mangindara, Mangindara; Hastuti, Hastuti; Ekawaty, Dian; Aprianti, Risma; Nurfadhilah, Nurfadhilah (Jurnal Abdimas Jatibara, 2025)
The patient registration process is the initial step in the creation of medical records at every healthcare facility. At this stage, the patient's personal identification data and the purpose of their visit to the hospital are recorded. This community service topic was chosen because many patients and their families still do not fully understand the outpatient registration procedures at hospitals. The method used in this community service activity is the production of an educational video that will be disseminated through the hospital. The results of this activity indicate an improvement in understanding of the outpatient services process, starting from registration to receiving medical care. This activity is highly important, considering that patients and their families require fast and accurate services. Therefore, education or socialization regarding the registration process is essential. With the presence of this educational and socialization video, it is expected that patients will find it easier to complete the registration process and access medical services.